A Novel Microbiological Method in Microtiter Plates for Screening Seven Kinds of Widely Used Antibiotics Residues in Milk, Chicken Egg and Honey - Wu, Qin; Peng, Dapeng; Liu, Qianying; Shabbir, Muhammad Abu Bakr; Sajid, Abdul; Liu, Zhenli; Wang, Yulian; Yuan, Zonghui (Frontiers in Microbiology, 2019)
A broad-spectrum microbiological inhibition method has been developed for rapidly screening different kinds of antibiotics such as β-lactam, aminoglycosides, tetracyclines, sulfonamides, macrolides, lincosamides and quinolones in milk, chicken egg and honey by using an easy sample preparation. The microbiological system in microtiter plates consists of an agar medium, a mixture of nutrients, test bacteria (Geobacillus stearothermophilus var C953), bromocresol purple, and other supplements such as trimethoprim, chloramphenicol, streptomycin and enrofloxacin which helps to improve the detection capability of the microbiological system towards the chosen antibiotics. It was observed that the limit of detection of the kit used in present study for all kinds of antibiotics in milk were lower than or close to maximum residue limits determined by EU or CODEX. For chicken egg and honey, the detection capability of the kit was similar to determined in milk. Moreover, it was revealed that the kit in present study was more sensitive to aminoglycosides, macrolides and quinolones in various matrixes than internationally available commercial kits. The false-positive and false-negative rates for both were 0 %. The coefficient of variations among various factors was all less than 4 %. Additionally, the quality guarantee period of the kit was more than 6 months at 4 ºC. A good correlation between the kit results and the LC–MS/MS results for milk was also observed, which revealed that the kit was reliable to screen antibiotics residues in incurred samples.